Agro corruption income insurance (2013)
Colombia , through negocion some FTAs has attempted integration with the global economy , but as we know clearly and openness brings advantages, it also involves the entry of products and services from those countries with which it is signed each negotiation , which implies that our country is ready to face this competition.